Religious Development for the Elderly in the Garut Griya Elderly Service Unit - Anton; Fiqra Muhamad Nazib; julistya (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the influence of religious activities on the spiritual well-being of elderly people living in social care institutions. Spiritual well-being is an important aspect of the lives of elderly people, especially in dealing with the various physical, psychological, and social changes that accompany the aging process. This study used a descriptive qualitative method with data collection techniques through observation, in-depth interviews, and documentation of informants consisting of elderly people, caretakers of the institution, and religious leaders. The results showed that religious activities, such as religious study, collective dhikr, and regular spiritual guidance have a positive impact on inner peace, enthusiasm for life, and a sense of meaning in life for the elderly. These activities also strengthen social relationships among residents of the institution and strengthen the spiritual dimension of the elderly in their old age. Supporting factors for religious activities include the availability of adequate worship facilities and infrastructure, a supportive social environment, and the active role of religious leaders as spiritual guides and motivators. Conversely, inhibiting factors include the elderly's weak physical condition, limited access to activities, and a lack of specialized assistance. Thus, the implementation of structured and sustainable religious activities is essential as part of a holistic approach to improving the quality of life of elderly people in social care institutions.